The role of the immune system in the initiation and persistence of the Euprymna scolopes-Vibrio fischeri symbiosis - McFall-Ngai, Margaret (2009)
The squid-vibrio symbiosis is an experimental system being studied as a model of the chronic colonization of animal epithelia by bacterial partners. One principal question being asked with this model is: what is the role of the immune system in the dynamics of the onset and maintenance of the symbiotic state? This review focuses upon results of research to date, which have demonstrated that both cell-mediated and cell-free components of the innate immune system are involved in these processes.